Too many Stages, Too Little Time: Bureaucratization and Potential Impasse in the Social Safety Net Program in Indonesia - Khaerul Umam Noer; Ni Loh Gusti Madewanti (Universitas Muhammadiyah Yogyakarta, 2020)
Since its first announcement in March 2020, the number of positive confirmed patients as well as patients under surveillance has increased exponentially. Recognizing the impact of Covid-19 on the poor, the government reallocated expenditure budget by increasing the amount of aid to the community. This paper focuses on social safety net policies, mainly in two programs: the Hope Family Program and the Sembako Program. Both of these aids are actually not any new programs, as they have been around since 2017, but the Covid-19 pandemic is adding to the economic burden of the household so that both of these aids are then increased in amount. Specifically, this paper focuses on two things. First, how the social safety net policy must be implemented according to the rules. Second, mapping the potential impasse that arises from the complexity of the policy itself. It is undeniable that the problem of bureaucratization always comes up more in every policy, with no exception for this social aid policy. By mapping out potential obstacles, this paper can provide a number of key solutions for resolving obstacles in the field.